Plasmonic refractive index sensor based on metal–insulator-metal waveguides with high sensitivity. Issue 9 (21st May 2019) - Butt, M. A.; Khonina, S. N.; Kazanskiy, N. L.
ABSTRACT: A plasmonic square ring resonator sensor design based on metal–insulator-metal waveguide is proposed. The transmission spectra and electric field distribution of the resonator are simulated using the finite element method (FEM). The numerical simulation results achieved from the transmission spectra are used to investigate the sensing characteristics of the structure. The effect of structural parameters on the spectral characteristics and sensing performance are investigated in detail. The sensitivity is obtained to a value as high as 1367 nm/RIU with a figure of merit of ∼25. The suggested design can possibly be applied in optical network-on-chip and on-chip nanosensors.